Cost-effectiveness analysis of increasing drug therapy coverage for patients with coronary artery disease in combination with atrial fibrillation and heart failure - V. I. Ignatieva; A. V. Kontsevaya; M. M. Lukyanov; V. G. Klyashtorny; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To make a cost-effectiveness analysis of increasing the prescription rate of combination therapy with beta-blockers (BBs), angiotensin-converting enzyme inhibitors or angiotensin receptor blockers (ACEIs/ARBs), statins and oral anticoagulants (OACs) in patients with coronary artery disease (CAD) in combination with atrial fibrillation (AF) and heart failure (HF).Material and methods. Based on the analysis of 6 medical registers, the proportion of patients with CAD in combination with AF and HF among all patients with CAD, and the prescription rate of BBs, ACEIs/ ARBs, OACs and statins, was assessed. Mortality and hospitalization rates were also determined in patients receiving only part of therapy or without it. In multivariate statistical models, the reduction in the risk of adverse events was calculated when all 4 drug groups were prescribed. Costs were calculated based on government procurement data and current compulsory health insurance rates. The obtained estimates were used to build a Markov model.Results. According to the modeling results, the number of patients with CAD in combination with AF and HF in the Russian Federation is 1,16-1,27 million people. When prescribing from 0 to 3 drug groups out of 4 required, the mortality rate was 115, and the hospitalization rate was 246 per 1000 patient-years. In the group of patients receiving all 4 groups of drugs, there was significant hazard ratio for death and hospitalization was 0,434 and 0,765, respectively. When modeling the prescription of drugs from all 4 groups in 1000 patients currently receiving only 0-3 groups of drugs, there was a reduction in the expected number of deaths by 52,3% (153 lives saved) and an expected number of hospitalizations by 16,0% (99 prevented hospitalizations) over 3 years. Additional costs per 1 life saved amounted to 515,3 RUB thousand.Conclusion. Patients with a combination of CAD, HF and AF are one of the groups with the highest risk of death and hospitalization for CVD. Modeling has shown that increasing coverage of this group of patients with appropriate therapy, including BBs, ACEIs/ARBs, statins and OACs, is a clinically and economically feasible solution.